Prevalence and impact of genital psoriasis. (1st March 2019) - Larsabal, M.; Ly, S.; Sbidian, E.; Moyal‐Barracco, M.; Dauendorffer, J.‐N.; Dupin, N.; Richard, M.A.; Chosidow, O.; Beylot‐Barry, M.
Summary: Psoriasis is a common chronic inflammatory skin disease, affecting about 3% of the general population and approximately 2.5 million people in France, where this study took place. The genital area may be affected, however prevalence is poorly understood, meaning we do not know exactly how commonly this occurs. While it affects quality of life, genital psoriasis is under‐recognized, probably due to the reluctance of patients to discuss genital involvement and sexual quality of life. The aims of this study, called the GENIPSO study, were to determine the prevalence of genital psoriasis, its clinical characteristics (its symptoms), whether it is associated with a particular type of psoriasis, and its impact on quality of life. The study included 776 adults seeing their doctor for psoriasis between November 2016 and March 2017. Among them, 336 (43.2%) had genital psoriasis. All these patients were aware that they had psoriasis on their genitals (genital lesions) but only 135 (40%) had already had a genital medical examination. Genital lesions were associated with (linked to) male gender, more severe psoriasis, first developing psoriasis when aged over 20 years, psoriasis of the skin folds, psoriasis on the scalp, nail and external auditory (ear) canal, but they were not associated with obesity or psoriatic arthritis. Itching was the main symptom. Genital psoriasis was associated with reduced quality of life and sexual health. The study found that genital psoriasis has a high prevalence in patients seeing their doctors about their psoriasis generally, it affects quality of life and should be better taken into account by dermatologists for the best possible care for patients.